Analysis of the costs of teleconsultation for the treatment of diabetes mellitus in the SUS - Frederica Valle de Queiroz Padilha; Daniela Laranja Gomes Rodrigues; Gisele Silvestre Belber; Marcos Aurélio Maeyama; Lígia Spinel; Ana Paula Neves Marques Pinho; Alessandra Vitti; Mariana Selbach Otero; Greta Barriquel Pompermaier; Tanise Balvedi Damas; Haliton Oliveira Junior (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE To present the results of a cost analysis of remote consultations (teleconsultations) compared to in-person consultations for patients with type 2 diabetes, in the Brazilian public healthcare system (SUS) in the city of Joinville, Santa Catarina (SC). In addition to the costs from the local manager's perspective, the article also presents estimates from the patient's perspective, based on the transportation costs associated with each type of consultation. METHOD Data were collected from 246 consultations, both remote and in-person, between 2021 and 2023, in the context of a randomized clinical trial on the impact of teleconsultation carried out in the city of Joinville, SC. Teleconsultations were carried out at Primary Health Units (PHU) and in-person consultations at the Specialized Health Center. The consultation costs were calculate by the method time and activity-based costing (TDABC), and for the estimate of transportation costs data was collected directly from the research participants . The mean costs and time required to carry out each type of consultation in different scenarios and perspectives were analyzed and compared descriptively. RESULTS Considering only the local SUS manager's perspective, the costs for carrying out a teleconsultation were 4.5% higher than for an in-person consultation. However, when considering the transportation costs associated with each patient, the estimated value of the in-person consultation becomes 7.7% higher and, in the case of consultations in other municipalities, 15% higher than the teleconsultation. CONCLUSION The results demonstrate that the incorporation of teleconsultation within the SUS can bring economic advantages depending on the perspective and scenario considered, in addition to being a strategy with the potential to increase access to specialized care in the public network.